In-silico and in-vitro studies revealed alpha-amyrin as a potent pnhibitor of TLR2 for the therapeutics of bacterial infection and sepsis: Alpha-amyrin as an effective inhibitor of TLR2 - Elgadir, Thoraya A-; El-Gamal, Basiouny; Ellatif, Mohamed Abd; Nasif, Khalid Ali; Omer, Safaa; Mohieldeen, Muniera; Patel, Ayyub A.; Amanullah, Mohammed; Malik, Arshi; Mahfouz, Ahmed A.; Shaamash, Ayman H.; Alsamghan, Awad S. (Cellular and Molecular Biology, 2024)
This study employed a multifaceted approach to investigate the inhibitory potential of alpha-amyrin against TLR2, a key player in bacterial infection and sepsis. A high-resolution TLR2 model was constructed using Swiss-MODEL, exhibiting excellent quality with 100% sequence identity and coverage. Cavity detection revealed five significant cavities on TLR2. Molecular docking identifies alpha-amyrin as a potent inhibitor, displaying a strong binding affinity of -8.6 kcal/mol. Comprehensive analyses, including ADMET predictions, PASS analysis, and SwissTargetPrediction, affirm alpha-amyrin’s drug-like properties and diverse biological activities. Cytotoxicity assays on HEK-293 cells confirm its safety, and fluorescence-based inhibition assays provide empirical evidence of its inhibitory potency on TLR2 enzymatic activity. Further validations in HUVECs show a significant decrease in TLR2 mRNA expression (p<0.01) and activity (p<0.05) upon alpha-amyrin treatment. In conclusion, this integrative study positions alpha-amyrin as a promising therapeutic candidate for TLR2 inhibition, emphasizing its potential in combating bacterial infections with safety and efficacy.